Assessing the job satisfaction of health workers in primary health centers in Anaocha, Anambra State in Nigeria (West African Journal on Sustainable Development, 2024)
Background: Determining the effectiveness of a health system is the presence of an adequate and well-distributed workforce of skilled health professionals, particularly within the Primary Health Care sector. These healthcare personnel constitute a significant portion of public health expenditure and with their jobs form the cornerstone of numerous policies and management approaches aimed at augmenting productivity and efficacy.Objective: This study sought to assess the level of job satisfaction among healthcare workers in Primary Health Centres in Anaocha LGA, Anambra State, Nigeria.Methods: After obtaining approval from the ethics and research committees in Nnamdi Azikiwe University Teaching Hospital, a cross-sectional study of 70 consenting Primary healthcare workers who met the eligibility criteria was conducted. They were selected by simple random sampling from 1st February to 1st March 2021 at the Primary Healthcare Centres in Anaocha Local Government Area (L.G.A) of Anambra State. Data collection was by the use of a self-administered, semi-structured questionnaire and analyzed using the statistical package for Social Sciences (SPSS) version 25.0. The level of significance for this study was set at P < 0.05 for all analyses.Results: The study showed a high level of overall job satisfaction, as 81.43% of the respondents were satisfied with their jobs. The workers' salary (p = 0.021), their physical working environment (p = 0.043), the distance of the workplace from their place of residence (p = 0.041), and payment of allowances (p = 0.012) were significantly associated with job satisfaction.Conclusion: This study demonstrated a notably elevated level of job satisfaction. Special allowance schemes should be instituted for primary healthcare workers to encourage their stay in rural areas.
Keywords: Job satisfaction; Healthcare workers; Primary Healthcare Centres; Nigeria